Orange pectin mediated growth and stability of aqueous gold and silver nanocolloids - Nigoghossian, Karina [UNESP]; Santos, Moliria Vieira dos [UNESP]; Barud, Hernane Silva [UNESP]; Silva, Robson Rosa da [UNESP]; Rocha, Lucas Alonso; Caiut, José Maurício Almeida; Assunção, Rosana Maria Nascimento de; Spanhel, Lubomir; Poulain, Marcel; Messaddeq, Younes [UNESP]; Ribeiro, Sidney José Lima [UNESP] (Elsevier B.V., 2015)
The role of orange based pectin in the nucleation and growth of silver and gold nanoparticles is addressed. Pectin is a complex polysaccharide found in fruits such as oranges, lemons, passion fruits or apples. It displays smooth and hairy chain regions containing hydroxyl-, ester-, carboxylate-and eventually amine groups that can act as surface ligands interacting under various pH conditions more or less efficiently with growing nanometals. Here, a high methoxy pectin (>50% esterified) was used as a stabilizer/reducing agent in the preparation of gold, silver and silver-gold nanoparticles. Commercial pectin (CP) and pectin extracted from orange bagasse (OP) were used. Optionally, trisodium citrate or oxalic acid we used to reduce AgNO3 and HAuCl4 in aqueous environment. Characterization methods included UV-vis absorption spectroscopy, transmission electron microscopy, electron diffraction and energy-dispersive X-ray spectroscopy. The results show that under different pH conditions, pectin and reducing agents allow producing various nanostructures shapes (triangles, spheres, rods, octahedrons and decahedrons) often with high polydispersity and sizes ranging between 5 nm and 30 nm. In addition, depending on Ag/Au ratio and pH, the surface plasmon bands can be continuously shifted between 410 nm and 600 nm. Finally, pectin seems to be a highly efficient stabilizer of the colloidal systems that show a remarkable stability and unchanged optical spectral response even after five years.
Keywords: Gold; Silver; Nanoparticle; Pectin